Manajemen stress selama pandemi covid 19 pada wirausaha - Utari Nur Khasanah; Putri Uswatun Khasanah; Isna Rahma Adhania; Hemalia Astikawati; Aftina Nurul Husna (Prosiding University Research Colloquium, 2022)
The purpose of this study was to explore information through case studies related to the management of women's work stress during the Covid-19 pandemic. This research method uses a qualitative method with a single instrumental case study approach. Data collection techniques used in this study were interviews, observation and documentation with 3 female entrepreneurs as sources. It can be concluded that the Covid-19 pandemic has had many impacts on all groups, especially a woman who has multiple roles in her life